Exploring the Perspective of Indonesian In-service Elementary Teachers toward Pedagogical Content Knowledge (PCK) on Teaching Mathematics - Nugraha, Trisna; Prabawanto, Sufyani (International Conference on Elementary Education, 2021)
Mathematical proficiency as a goal of learning mathematics and other skills developed by teachers in schools through a didactic and pedagogical activity. The quality of teaching mathematics in elementary education is largely determined by the teacher's perspective on Pedagogical Content Knowledge (PCK) in mathematics learning itself. This study aims to see the perspectives of elementary school teachers who are experienced in teaching mathematics regarding several things that are needed in learning mathematics in elementary schools. The study used a survey method which was conducted on elementary school teachers who have experience in teaching mathematics with various educational backgrounds and different schools (n = 65) through random sampling. The study is focused on investigating the pedagogical perspective, the perspective of mathematics learning objectives, and the perspective of mathematics content taught in elementary schools. These perspectives are arranged in a research instrument in the form of a questionnaire containing multiple answer questions and open-ended answers. Data collection was carried out with the help of google forms. The data analysis used is quantitative and qualitative approaches. The results showed that various innovative learning models were known by the teacher, although not all teachers were sure that they had implemented the learning model according to the syntax of the learning model. Also, teachers are still optimistic that innovative learning models have flexibility so that they can be applied in pandemic conditions.